Behavioural risk factors for non communicable diseases among adults in Kerala, India - T.N. Sugathan, C.R. Soman & K. Sankaranarayanan (Indian J Med Res 127, June 2008, pp 555-563, 2008)
Background & objectives: Cardiovascular and other chronic diseases are becoming the major causes of morbidity and mortality in most of the third world countries including India, especially in the southern Indian States, like Kerala, where most of the health indicators match closely with those of any developed country. Various behavioural risk factors (BRF) namely smoking, unhealthy diet, stress at home and work place, consumption of alcohol, sedentary life style, etc., are known to be risk factors for many such diseases. The present study was carried out to estimate the prevalence of various behavioural risk factors for chronic diseases, and to identify their biosocial correlates. Methods: A cross-sectional study was done in which the data were collected from a sample of 6579 individuals of age 30 to 74 yr, randomly selected following a stratified multi-stage cluster sampling design covering Kerala State. The important factors investigated include various behavioural risk factors, presenting chronic diseases and family histories among close relatives. The data were analysed using both univariate and multivariate analyses. Results: The two major risk factors observed among males were smoking and alcohol consumption. About two fifths (40per cent) of them were current smokers as well as current users of alcohol (41 per cent). The median age at initiation was 21 yr for both smoking habits and for alcohol consumption. Nearly a quarter of the target population were inactive based on work and leisure time activities. More than one-fifth of them reported stress. Obesity was found more among females than males. Low socio-economic background was found to be a high predictor (high risk group) for habit of smoking, alcohol consumption, stress and unhealthy diet. Interpretation & conclusions: Substantially high levels of the various behavioural risk factors among adults in Kerala suggests an urgent need for adopting healthy life style modifications among the population in general. The increased risk observed among the younger generation for behavioural risk factors such as smoking and alcohol consumption calls for urgent corrective steps and measures for long-term monitoring of all major risk factors as well as the major chronic disease conditions